Ancora un plagio in Italia del Tirant lo Blanc: la lettera dedicatoria alla Tragicocomedia di Calisto e Melibea (1506). - GESIOT, JACOPO (Scripta, 2019)
The first translation of La Celestina appears in Rome in 1506 and it was furnished with a dedicatory letter by the translator, mostly composed of plagiarized fragment from Tirant lo Blanc by Joanot Martorell. The present article aims to publicize this stratagem and especially to explain the reason of this fusion: in the early of 15th century the reading of Tirant, besides the amusement, preserves its educational purpose, as we can see from the didactic intent of the first translator of some excerpts from Martorell: Alfonso Ordóñez.